Tacipi Limestone Facies Distribution and Sequence Development, Mio-Pliocene, South Sulawesi, Indonesia - Alit A. Ngakan; Neil Harbury (Berita Sedimentologi, 1997)
The tectonic evolution of Sulawesi is complex it is situated in the triple junction of the Indo-Australian, Eurasian and Pacific Plates. The late Cretaceous to Neogene history has resulted in considerable changes in the tectonic setting attributable to plate motions. Southern Sulawesi was a fore-arc region in the late Cretaceous with the deposition of a deep marine siliciclastic sequence; this evolved into a back arc setting in the Eocene, and a thick succession of volcanics of both acidic and basin composition were developed from Eocene to lower Miocene times. Following this volcanic phase carbonate sedimentation dominated in the Middle Miocene. This study documents the tectonic control on carbonate facies distribution (Tacipi and Walanae Formations) in the Middle Miocene-Lower Pliocene of southern Sulawesi.